О принципах фонологического анализа дифтонгов в синхронии и диахронии - Забулене, Л. (Kalbotyra, 1976)
The analysis of diphthongs offers considerable difficulties both from the phonetic and phonological point of view. We still lack a more complete and uniform theory and find a great variety of opinions and approaches, some of which are often contradictory. It should be noted that from the very outset scholars have pointed out the phonic complexity as a characteristic peculiarity of diphthongs.The main problem of the phonological analysis of diphthongs is the question of the distinctiveness of gliding. The most important point to decide is whether gliding is a distinctive feature, or only a subphonemic non-distinctive feature in the phonetic realization of monophthongs, or whether both components represent a biphonemic combination of monophthongs. It should be noted that only the technique of combining different phonetic, phonological and morphological criteria may prove to be really effective both in synchrony and diachrony. P articular stress should be laid on the fact that a due regard for the general phonological system should serve as the giding principle of the analysis.